Antithrombotic Therapy in Myocardial Infarction: Historic Perils and Current Challenges—A 70-Year Journey - Fernando, Himawan; McFadyen, James D.; Palasubramaniam, Jathushan; Shaw, James; Wang, Xiaowei; Stub, Dion; Peter, Karlheinz (Thrombosis and Haemostasis, 2020)
There have been numerous and intriguing advancements in antithrombotic therapy for myocardial infarction since it was described in the earliest issues of Thrombosis and Haemostasis. In this article, we revisit historical breakthroughs and describe the four most challenging contemporary themes relating to antithrombotic therapy in myocardial infarction. In all four, the challenge is to find the best balance of reducing specific levels of ischaemic risks without increasing bleeding risk. The first is the question of the optimal duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI). This includes discussion of monotherapy after a period of DAPT. The second relates to the role of genotype and phenotype-guided individualisation of antiplatelet therapy. There is emerging evidence for a role of pheno/genotyping in identifying individuals at high risk for recurrent ischaemic events or in guiding the timing of cardiac surgery for patients on DAPT. The third addresses the increasing evidence for dual pathway inhibition, for example, with rivaroxaban in addition to aspirin in patients where high ischaemic and low bleeding risk is demonstrated. Finally the fourth highlights the challenge of the most appropriate combination of antiplatelet and anticoagulation therapy for patients with known atrial fibrillation after PCI. In most individuals, oral P2Y12 inhibitor therapy combined with a direct acting oral anticoagulant appears to be the best strategy based on the available evidence. Overall, the progress in antithrombotic therapy achieved over the last seven decades is remarkable, however, there are important issues to address and progress still to be made.
Keywords: myocardial infarction; combination antiplatelet anticoagulation therapy; dual pathway inhibition; dual antiplatelet therapy; platelet function testing